Investigation of natural convection of magnetic nanofluid in an enclosure with a porous medium considering Brownian motion. (September 2019) - Dogonchi, A.S.; Seyyedi, Seyyed Masoud; Hashemi-Tilehnoee, M.; Chamkha, Ali J.; Ganji, D.D.
Abstract: In this work, magnetic nanofluid natural convection in the porous enclosure considering Brownian motion is studied numerically using Control Volume Finite Element Method (CVFEM). The effective viscosity and thermal conductivity of nanofluid are specified by Corcione correlation in which the impact of Brownian motion on the thermal conductivity is considered. The considered porous enclosure is heated from the inner circular side and it cooled from the outer circular side while two other walls are insulated. The impacts of various controlling parameters such as the Rayleigh number, Hartmann number, Darcy number and angle of magnetic field parameter are examined on the streamlines and isotherms. In addition, the average and local Nusselt numbers are obtained and presented via figures. The results state that the intensity of the convective flow has a direct relationship with the Rayleigh number and Darcy number while it has a reverse relationship with the Hartmann number and inclination angle of the magnetic field.